"Vibrant Entanglements": HIV Biomedicine and Serodiscordant Couples in Papua New Guinea. Issue 3 (3rd April 2019) - Persson, Asha; Kelly-Hanku, Angela; Bell, Stephen; Mek, Agnes; Worth, Heather; Nake Trumb, Richard
ABSTRACT: The global ambition to "end AIDS" hinges on the universal uptake of HIV treatment-as-prevention and is undergirded by the assumption that biomedical technologies have consistent, predictable effects across highly diverse settings. But as anthropologists argue, such technologies are actively transformed by their local encounters, with various constitutive effects. How priority populations, such as HIV "serodiscordant" couples, negotiate treatment-as-prevention remains relatively unknown. We consider the "vibrant entanglements" that can shape couples' engagement with global biomedical technologies in the local context of Papua New Guinea (PNG)—a relatively uncharted biomedical landscape—and what we hope our current research in this setting will achieve.